(untitled) (African Human Mobility Review, 2021)
The case-study literature on refugees and asylum-seekers in South Africa is dominated by an overwhelming focus on the problems they face and their marginalised existence, reinforcing an image of victimhood, exploitation and vulnerability. In this paper, we seek to broaden the image of refugees and their economic impacts beyond a narrow focus on their marginal status and vulnerable position. They are viewed here as dynamic agents with skills and capabilities who can play an integral role in transforming local settings and contributing to economic development. This paper presents and discusses the results of a survey of over 1,000 refugee informal business-owners in Cape Town and small-town Limpopo.